University and Entrepreneurship: An Empirical Investigation in the Tunisian Context - Ali, Tarek Ben (International Review of Management and Marketing, 2017)
Higher education in Tunisia is currently confronted with the explosion of students’ number. This significant growth represents an important challenge to take up: improving the quality of education and its relevance to the labour market and promote entrepreneurial culture and firm creation. In this context, we investigate the entrepreneurial intentions of final-year university students in the Tunisian economy by applying the theory of planned behavior (TPB). The objectives of the study were to test whether the TPB can help explain the entrepreneurial intentions of university students; to determine whether students will have intentions to start a business and to identify the key determinants of each antecedent of entrepreneurial intention. Data was analyzed by means of the SPSS using descriptive statistics, hierarchical multiple regression analysis and principal components analysis. In line with the TPB, the attitude towards becoming an entrepreneur, perceived behavioural control and subjective norms were statistically significantly associated with entrepreneurial intention. Most of the Tunisian students indicated that they intended to start businesses as soon as they had completed their studies. Furthermore, some key determinants of each antecedent of entrepreneurial intention had been proposed as entrepreneurship educators to the Tunisian authorities to improve entrepreneurship and the creation of firms. Keywords: Entrepreneurship, University Students, Theory of planned behavior, Principal component analysis, multiple regression analysis JEL Classification: M130